The influence of some factors on the characteristics of metallized incendiary mixtures - Le Viet Ha; Nguyen Mau Vuong; Nguyen Xuan Thanh; Nguyen Duy Tuan (Journal of Military Science and Technology, 2023)
In this article, the influence of some factors on the characteristics of metallized incendiary mixtures (pyrogels) was studied. The pyrogel-type contains benzene, polyisobutylene, magnesium, aluminum-magnesium alloy, sodium nitrate, and different additives. It is shown that the molecular weight of polyisobutylene, the amount of aluminum-magnesium alloy, the particle size of metal combustibles, and the amount and type of polyester threads have different effects on the heat of combustion, flash point, burning rate, flame height, and adhesion to the material surface. The optimal pyrogel contains 38-40% thickened benzene - PIB with molecular weight 175000-225000, 25-27% aluminum-magnesium alloy with particle size ≤ 160µm, 10-12% magnesium powder with particle size ≤ 180µm, 15% sodium nitrate, 8% phenol-formaldehyde resin and 1.5% (over 100%) 3D polyester threads.